Wheat varietal flours: Influence of pectin and DATEM on dough and bread quality - Ponzio, Nora Raquel (2013)
The effect of two additives, high methoxyl pectin (P) and the emulsifier diacetyl tartaric acid esters of monoglycerides commonly named DATEM (D) and their mixture (P+D) on dough properties and baking performance of two varietal Argentinean wheat flours (Buck Pronto [BP]; Klein Escudo [KE] was analyzed. Rheological characterization of dough (alveogram, farinograms, texture profile analysis-TPA, and rheometric assays), with and without additives, was performed. SEM was used to evaluate the microstructure of dough. Baking performance was analysed by bread volume measurements, shape ratio of loaves (width/height), and the hardness of crumb and crust. Assays on dough showed differences in alveographic force (W) and in most of the texture profile analysis parameters. Assays on bread showed that BP specific volume was improved with the addition of P and P+D, but shape ratio was only improved with the mixture of P+D. Breads from KE flour with additives presented, in all cases, showed higher volumes and a better shape ratio than those obtained with the control sample. Hardness of KE crumb was diminished by all additives but BP crumb was softened only with the addition of P and P+D. All sensory parameters were improved for both types of bread, particularly with D and P+D.